2016
DOI: 10.1038/srep27530
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of oxidative stress and subsequent induction of apoptosis and endoplasmic reticulum stress allows citral to decrease cancer cell proliferation

Abstract: The monoterpenoid, citral, when delivered through PEG-b-PCL nanoparticles inhibits in vivo growth of 4T1 breast tumors. Here, we show that citral inhibits proliferation of multiple human cancer cell lines. In p53 expressing ECC-1 and OVCAR-3 but not in p53-deficient SKOV-3 cells, citral induces G1/S cell cycle arrest and apoptosis as determined by Annexin V staining and increased cleaved caspase3 and Bax and decreased Bcl-2. In SKOV-3 cells, citral induces the ER stress markers CHOP, GADD45, EDEM, ATF4, Hsp90,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 28 publications
(46 reference statements)
4
44
0
Order By: Relevance
“…ER stress is reported to induce the activation of BIM via IRE1a/JNK, IRE1a/CHOP, or PERK/ATF4/CHOP pathways (18,35). Usually, ER stress is induced by oxidative agents that modulate cancer cell survival (36). Consistent with these reports, we found that ER stress induced by genipin markedly upregulates BIM by inducing the IRE1a/JNK/BIM pathway in colorectal cancer cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…ER stress is reported to induce the activation of BIM via IRE1a/JNK, IRE1a/CHOP, or PERK/ATF4/CHOP pathways (18,35). Usually, ER stress is induced by oxidative agents that modulate cancer cell survival (36). Consistent with these reports, we found that ER stress induced by genipin markedly upregulates BIM by inducing the IRE1a/JNK/BIM pathway in colorectal cancer cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism of action of citral is due to its geranial isoform component (Nakamura et al, 2003). Recent studies have shown citral to inhibit cell intracellular levels of oxygen radicals and, consequently, by the modulation of cellular oxidative status, leading to reduction of cancer cell proliferation and ultimately resulting in cell death (Kapur et al, 2016;Sanches et al, 2017). Citral was also shown to induce caspase activation and subsequent apoptosis induction in several cancer cell types, including colorectal cancer and glioblastoma (Dudai et al, 2005;Queiroz et al, 2014;Sheikh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Inducer of the glutathione-Stransferase enzyme, geranial induce apoptosis and inhibit the promotion of skin cancers (Kapur et al, 2016).…”
Section: Relationship Between Antimicrobial Activity Of Mouthwashes Amentioning
confidence: 99%